Invitation only murder [large type] - Meier, Leslie (Meier, Leslie. Lucy Stone mystery., 2019)
"Lucy doesn't know what to expect as she arrives on a private Maine island owned by eccentric billionaire Scott Newman, only that the exclusive experience should make for a very intriguing feature story. An avid environmentalist, Scott has stripped the isolated property of modern conveniences in favor of an extreme eco-friendly lifestyle. A trip to Holiday Island is like traveling back to the nineteenth century, and it turns out other residents aren't exactly enthusiastic about living without cell service and electricity . . . Before Lucy can get the full scoop on Scott, she is horrified to find one of his daughters dead at the bottom of a seaside cliff. The young woman's tragic end gets pinned as an accident, but a sinister plot unfolds when there's a sudden disappearance . . . Stuck on a clammy island with murder suspects aplenty, the simple life isn't so idyllic after all. Now, Lucy must tap into the limited resources around her to outwit a cold-blooded killer--before it's lights out for her next!"--Provided by publisher of standard print edition.